2015
DOI: 10.5146/tjpath.2015.01312
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the cytological assessment of thyroid nodules

Abstract: Fine needle aspiration of thyroid has been used for years in a multidisciplinary approach, to diagnose different entities, in preventing over or under treatment of thyroid nodules. The widespread use of this methodology can be confirmed if "thyroid fine needle aspiration" is searched on PubMed, which results in over 5000 papers. In this manuscript, we aimed to focus on pitfalls in the evaluation of thyroid aspirations, covering cystic, inflammatory lesions, follicular lesions, oncocytic lesions, papillary carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 48 publications
2
56
0
2
Order By: Relevance
“…According to their study, convoluted nuclei might be a new clue of PTC. In concordance with some studies, such as Stamaki et al [6], Canberk et al [14], Kefeli et al [18], our study revealed that nucleus of PTC appeared to be large, oval, hypochromic, with small eosinophilia nucleoli, nuclear groove and pseudo inclusion. Dark-staining, "sticky" colloid (chewing gum-like) also can be observed but this finding is non-specific [14].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…According to their study, convoluted nuclei might be a new clue of PTC. In concordance with some studies, such as Stamaki et al [6], Canberk et al [14], Kefeli et al [18], our study revealed that nucleus of PTC appeared to be large, oval, hypochromic, with small eosinophilia nucleoli, nuclear groove and pseudo inclusion. Dark-staining, "sticky" colloid (chewing gum-like) also can be observed but this finding is non-specific [14].…”
Section: Discussionsupporting
confidence: 80%
“…In some of them, small nucleolus might be observed and there were no colloid ( Figure 9). In concordance with the study of Canberk et al [14], main findings were uniformly distributed cells, salt and pepper sign of chromatin, sporadically existence of amyloid on the ground, plasmocytoid, spindle, polygonal cells in TP smears from the medullary carcinoma. Presence of cellular structure in the aspirate is an important finding.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Owing to this reason, clinicians must keep the pathologist informed and immunohistochemistry must be performed. 11 In the diagnosis of MTC, calcitonin, chromogranin A, or CEA immunostaining can be used. 8 Calcitonin is an important molecule because it has a very significant role in the diagnosis and clinical followup of patients with MTC.…”
Section: Discussionmentioning
confidence: 99%
“…One of these is a paraganglioma-like pattern. 9,11 Another type of NE cancer is an extra-adrenal parasympathetic paraganglioma that is usually found in the head and neck region. These type of paragangliomas are usually non-functional tumors (95%).…”
Section: Introductionmentioning
confidence: 99%